Analysis of Soil Categories on Seismograf Sensor in Java Island Based on Ground Predominant Period and Vs30 - Wibowo, Nugroho Budi; Nurhaci, Dian Susri (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2015)
The aim of this research is to analyze the categorization of soil at sensor site locations based on predominant period of the ground and Vs30. This study was conducted at nine sites seismograph sensors in Java and Madura. Data processing method is using HVSR (Horizontal to Vertical Ratio) based on the SESAME European research project. The Java and Madura Vs30’s data were obtained from the USGS. This study utilizes the criteria of JRA 1990 and BSSC 2000 were used to determine the soil categories. It is found that the criteria of JRA 1900 and BSSC 2000 satisfies some sites namely LEM, KMMI, UGM and WOJI. The site of LEM and UGM have a soil that can be categorized in C type (dense soil / sand to soft rock) with dense soil conditions to the rock weathering process. Site KMMI can be categorized in D type (stiff soil) with dense soil conditions. Whereas the site WOJI can be categorized in A + B type (Hard rock and firm to hard rock) with hard rock conditions.